The effects of sapphire nitridation on GaN growth by metalorganic chemical vapour deposition - 乐伶聪 赵德刚 吴亮亮 邓懿 江德生 朱建军 刘宗顺 王辉 张书明 张宝顺 杨辉 (Chinese physics B, 2011)
In situ optical reflectivity measurements are employed to monitor the GaN epilayer growth process above a lowtemperature GaN buffer layer on a c-plane sapphire substrate by metalorganic chemical vapour deposition. It is found that the lateral growth of the GaN islands and their coalescence are promoted in the initial growth stage if optimized nitridation time and temperature are selected when the substrate is pre-exposed to ammonia. As confirmed by atomic force microscopy observations, the quality of the CaN epilayers is closely dependent on the surface morphology of the nitridated buffer layer, especially grain size and nucleation density.